Changes in Pore-Size Distribution and Hydraulic Conductivity of Compacted Soils by Grass-Derived Hydrochar - Dong, Huan; Leung, Anthony Kwan; Chen, Rui; Lourenco, Sergio; Kamchoom, Viroon (My University, 2023)
Hydrochar is a biomass-derived carbon-rich material produced by the hydrothermal carbonization process which requires less energy than the pyrolysis production of biochar. The effectiveness of using hydrochar to amend soil properties, especially hydraulic conductivity, and the underlying mechanism that hydrochar follow remain unknown. This study measured the effects of grass feedstock and grass-derived hydrochar produced at two temperatures (180°C and 240°C) on the pore size distributions (PSDs) and saturated hydraulic conductivity (ks) of compacted silty-clay sand. Hydrochar affected the ks through predominantly the change of macropores of amended soil. Specifically, the addition of 180°C hydrochar [with a 60% specific gravity (GHs) of the soil] at the mass proportion (fH) of 2.5% evolved the PSD from unimodal to trimodal, creating a more open soil structure and increasing the ks by more than half an order of magnitude. When fH exceeded the threshold of 2.5%, the improvement of ks decreased in effectiveness following the compression of macropores. The 240°C hydrochar that has a larger GHs (than the 180°C case) has a high threshold of 5% and introduced a great increase in ks. Test results highlight the importance of avoiding adding excessive hydrochar to prevent the reduction of the effectiveness of drainage improvement.
Keywords: Compacted soil; Hydraulic conductivity; Hydrochar; Pore size distribution (PSD)